RUNX2 enhances bladder cancer progression by promoting glutamine metabolism - Zhigang Huang; Bin Liu; Xiaoju Li; Chenghua Jin; Quansen Hu; Zhiwei Zhao; Yimin Sun; Qian Wang (Neoplasia: An International Journal for Oncology Research)
Bladder cancer is a prevalent malignancy within the urinary system. Prior research has suggested that glutamine metabolism plays a crucial role in driving bladder cancer progression. However, the precise molecular mechanism governing glutamine metabolism in bladder cancer is still inadequately understood. The research revealed a significant correlation between high levels of RUNX2 and SLC7A6 and advanced clinical stage, as well as poor prognosis, in bladder cancer patients. Furthermore, manipulating the levels of RUNX2 through overexpression or silencing demonstrated a significant impact on glutamine and bladder cancer progression. Mechanically, RUNX2 regulates the transcription of SLC7A6, resulting in enhanced glutamine metabolism and promoting the progression of bladder cancer. Overall, this research affirms the crucial function of RUNX2 as a key transcription factor to promoting glutamine and cancer development through modulation of SLC7A6. Targeting RUNX2 could represent a promising therapeutic approach for addressing aberrant glutamine metabolism in bladder cancer.